2023
DOI: 10.3389/fncel.2023.1084803
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbon reception by sensory neurons in basiconic sensilla of the Japanese carpenter ant

Abstract: To maintain the eusociality of a colony, ants recognize subtle differences in colony-specific sets of cuticular hydrocarbons (CHCs). The CHCs are received by female-specific antennal basiconic sensilla and processed in specific brain regions. However, it is controversial whether a peripheral or central neural mechanism is mainly responsible for discrimination of CHC blends. In the Japanese carpenter ant, Camponotus japonicus, about 140 sensory neurons (SNs) are co-housed in a single basiconic sensillum and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Odor coding is also shaped by interactions between neurons. The basiconic sensilla of the ant antennae can be innervated by dendrites from >100 individual OSNs, and studies in carpenter ants suggest that these neurons are electrically coupled via gap junctions ( 24 , 25 ). Any age-dependent changes in OSN peripheral connectivity are likely to alter odor responses as measured from AL calcium imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Odor coding is also shaped by interactions between neurons. The basiconic sensilla of the ant antennae can be innervated by dendrites from >100 individual OSNs, and studies in carpenter ants suggest that these neurons are electrically coupled via gap junctions ( 24 , 25 ). Any age-dependent changes in OSN peripheral connectivity are likely to alter odor responses as measured from AL calcium imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The basiconic sensilla of the ant antennae can be innervated by dendrites from >100 individual OSNs, and studies in carpenter ants suggest that these neurons are electrically coupled via gap junctions. 24 , 25 Any age-dependent changes in OSN peripheral connectivity are likely to alter odor responses as measured from AL calcium imaging. In addition, refinement of neuronal architecture within the AL network during adulthood could alter calcium activity in OSN afferents via changing signal input strength or the dynamics of presynaptic modulation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally there is existence of gap junctions between these OSNs, potentially providing lateral inhibition through electrical and ephaptic coupling (Takeichi et al ., 2018). It was thereby suggested that the BaS might act as an intensity filter at the periphery of the olfactory system ensuring a low response probability for the evaluation of concurrent and countervailing olfactory cues (Ng, Wu & Su, 2020; Watanabe et al ., 2023).…”
Section: Specialised Sensory System For Chcs?mentioning
confidence: 99%